Serotonin transporter density in isolated rapid eye movement sleep behavioral disorder - Garwood, Mark; Vijayakumar, Punithavathy; Bohnen, Nicolaas I.; Koeppe, Robert A.; Kotagal, Vikas (Frontiers in Sleep, 2024)
Background/Objective: The serotoninergic nervous system is known to play a role in the maintenance of rapid eye movement (REM) sleep. Serotoninergic projections are known to be vulnerable in synucleinopathies. To date, positron emission tomography (PET) studies using serotonin-specific tracers have not been reported in isolated REM sleep behavior disorder (iRBD).We conducted a cross-sectional imaging study using serotonin transporter (SERT) 11 C-3-amino-4-(2-dimethylaminomethyl-phenylsulfaryl)-benzonitrile (DASB) PET to identify differences in serotonin system integrity between 11 participants with iRBD and 16 older healthy controls.Results: Participants with iRBD showed lower DASB distribution volume ratios (DVRs) in the total neocortical mantle (1.13 (SD: 0.07) vs. 1.19 (SD: 0.06); t=2.33, p=0.028), putamen (2.07 (SD: 0.19) vs. 2.25 (SD: 0.18); t=2.55, p=0.017), and insula (1.26 (SD: 0.11) vs. 1.39 (SD: 0.09); t=3.58, p=0.001). Paradoxical increases relative to controls were seen in cerebellar hemispheres (0.98 (SD: 0.04) vs. 0.95 (SD: 0.02); t=2.93, p=0.007). No intergroup differences were seen in caudate, substantia nigra, or other brainstem regions with the exception of the dorsal mesencephalic raphe (3.08 (SD: 0.53) vs. 3.47 (SD: 0.48); t=2.00, p=0.056) that showed a non-significant trend towards lower values in iRBD.Conclusions: Insular, neocortical, and striatal serotoninergic terminal loss may be common in prodromal synucleinopathies before the onset of parkinsonism or dementia.Given our small sample size, these results should be interpreted as hypothesisgenerating/exploratory in nature.